Plasma Proteins as Biomarkers of Mortality After Total Body Irradiation in Mice. Issue 2 (17th April 2020) - Fu, Hanjiang; Xue, Yong; Su, Fei; Ding, Kexin; Wang, Yuan; Yu, Haiyue; Zhu, Jie; Li, Qing; Ge, Changhui; Zheng, Xiaofei
During large-scale acute radiation exposure, rapidly distinguishing exposed individuals from nonexposed individuals is necessary. Identifying those exposed to high and potentially lethal radiation doses, and in need of immediate treatment, is especially important. To address this and find plasma biomarkers to assess ionizing radiation-induced mortality in the early stages, mice were administered a whole-body lethal dose of γ radiation, and radiation-induced damage was evaluated. Multiple blood biomarkers were screened using an antibody array, followed by validation using enzyme-linked immunoassay. The results revealed that irradiation (IR)-induced mortality in mice and caused body weight and blood platelet losses in deceased mice compared to surviving mice. The levels of certain proteins differed after IR between these 2 groups. Specific proteins in preirradiated mice were also found to potentiate radiosensitivity. Plasma levels of interleukin (IL)-22, urokinase, resistin, and IL-6 were associated with radiation-induced mortality in irradiated mice and may be useful as potential mortality predictors. Our results suggest that estimating the levels of certain plasma proteins is a promising alternative to conventional cytogenetic biodosimetry to accurately identify individuals exposed to high radiation doses and those at risk of death due to exposure. This strategy would facilitate the rapid triage of individuals requiring immediate and intensive medical treatment.